2015
DOI: 10.1080/02255189.2015.1066666
|View full text |Cite
|
Sign up to set email alerts
|

The production of soft power: practising solidarity in Brazilian South–South development projects

Abstract: To cite this article: Sandra Bry (2015): The production of soft power: practising solidarity in Brazilian South-South development projects, Canadian Journal of Development Studies / Revue canadienne d'études du développement, ABSTRACT Brazil's development cooperation and solidarity discourse have been portrayed as soft power resources. However, few studies have analysed how Brazil implements development cooperation, and soft power theory itself suffers from a lack of empirical evidence. This article looks at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As Robledo (2015, p. 3) notes, in practice the motivation to provide foreign aid often results from a conflict between the moral obligation of the donor and the desire to advance its national interest. Frequently, foreign aid is seen as being driven by the strategic interests of donor states (Schraeder, Hook & Taylor, 1998), and as an instrument to advance the national interest in terms of power and geostrategic interests (Morgenthau, 1962, p. 301), becoming a form of "soft" power (Bry, 2015;Gallarotti, 2011). From this realist perspective, SSC can be seen as a strategy used by the South to secure or increase power; and to elevate their influence in the international arena (Jules & de s a e Silva, 2008, p. 53).…”
Section: South -South Cooperationmentioning
confidence: 99%
“…As Robledo (2015, p. 3) notes, in practice the motivation to provide foreign aid often results from a conflict between the moral obligation of the donor and the desire to advance its national interest. Frequently, foreign aid is seen as being driven by the strategic interests of donor states (Schraeder, Hook & Taylor, 1998), and as an instrument to advance the national interest in terms of power and geostrategic interests (Morgenthau, 1962, p. 301), becoming a form of "soft" power (Bry, 2015;Gallarotti, 2011). From this realist perspective, SSC can be seen as a strategy used by the South to secure or increase power; and to elevate their influence in the international arena (Jules & de s a e Silva, 2008, p. 53).…”
Section: South -South Cooperationmentioning
confidence: 99%
“…Nye influentially described soft power as the ability to use persuasion or cooptation via lower priority areas, especially culture, to shape the ideologies, preferences, and behaviors of other states 36 . Since its original formulation, this concept has been widely used by international relations scholars to analyze cooperation between states, including in relation to global health 37,38 .…”
Section: S39mentioning
confidence: 99%
“…So, nations must often be able to carve themselves a specific niche within the diplomatic world if they want to exert soft power; for this particular aspect, development is a popular field. Brazil, for example, has engaged in solidarity development cooperation, and evidence has shown that a more positive image of Brazil amongst aid recipients has formed not on the basis of what has been achieved via the project but more on how the management and relationship between entities and individuals were developed and sustained (Bry 2015). The development of a style, of a presence and of a voice is also what Norway has been recently cultivating.…”
Section: Unique Ways To Consider Soft Power? Niche and Growth Diplomacymentioning
confidence: 99%